2022
DOI: 10.3390/molecules27217214
|View full text |Cite
|
Sign up to set email alerts
|

The Design of 3D-Printed Polylactic Acid–Bioglass Composite Scaffold: A Potential Implant Material for Bone Tissue Engineering

Abstract: Bio-based and patient-specific three-dimensional (3D) scaffolds can present next generation strategies for bone tissue engineering (BTE) to treat critical bone size defects. In the present study, a composite filament of poly lactic acid (PLA) and 45S5 bioglass (BG) were used to 3D print scaffolds intended for bone tissue regeneration. The thermally induced phase separation (TIPS) technique was used to produce composite spheres that were extruded into a continuous filament to 3D print a variety of composite sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Possibly, the biomimetic composites were able of stimulating bone metabolism, especially due to osteoconductive properties and ability to attract cells of BG. 11,16 Additionally, the collagenic part possibly served a matrix for sustaining cell growth. Associated to all these positive effects, the BMSCs may have differentiated in pre-osteoblastic cells and osteoblast, which possibly resulted in a higher newly formed bone deposition in the region of the defect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the biomimetic composites were able of stimulating bone metabolism, especially due to osteoconductive properties and ability to attract cells of BG. 11,16 Additionally, the collagenic part possibly served a matrix for sustaining cell growth. Associated to all these positive effects, the BMSCs may have differentiated in pre-osteoblastic cells and osteoblast, which possibly resulted in a higher newly formed bone deposition in the region of the defect.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] In addition, the inclusion of an organic material such as collagen (COL) to BG, constituting a biomimetic with a similar composition to bone tissue, has also demonstrated very promising results for bone tissue healing. [12][13][14][15][16] COL, mainly type I, is one of the key components of the extracellular matrix (ECM) in vertebrates, with important mechanical and biological roles. 14,17 Furthermore, many authors evidenced the positive effects of BG/COL composites on the acceleration of bone formation and tissue healing in experimental models of bone defects in rats.…”
Section: Introductionmentioning
confidence: 99%
“…PLA is a thermoplastic and biodegradable polymer commonly used as a 3D printing material. Its strong biomechanical properties make it ideal for bone tissue engineering [34][35][36]. In our study, we used PLA as our 3D printing biomaterial and found that different infill densities would produce scaffolds with different porosity.…”
Section: Discussionmentioning
confidence: 99%
“…Various degradable polymers, including poly-acrylonitrile butadiene styrene (ABS), polycaprolactone (PCL), polylactic acid (PLA), polyglycolic acid (PGA), and chitosan, can be used to fabricate 3D scaffolds [28][29][30][31][32][33]. Among these materials, PLA is a thermoplastic and biodegradable aliphatic polyester derived from a naturally organic acid and possesses excellent mechanical properties, making it an ideal material in bone tissue engineering [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Sultan et al 47 PLA2003D45S5 BG Solvent based 3D printing Developed composite has a biomimetic structure and mechanical properties and can be used in bio implants for soft as well as hard tissue engineering.…”
Section: Biological Analysismentioning
confidence: 99%